ENHANCING THE FAMILY’S QUALITY TIME AS A WORK OF PREVENTION TO CHILD ABUSE IN THE PANDEMIC PERIOD - Amatullah Asma Ashilah; Maisaroh Maisaroh; Fahrul Fauzi (Psychosophia: Journal of Psychology, Religion, and Humanity, 2020)
The purpose of this study is to offer solutions related to the prevention of domestic violence, especially those related to children, through improving the quality of children's relationships with their parents. This research departs from the increasing number of violence occurring in the household realm, especially during the Covid-19 pandemic, which causes individuals to remain at home. The research method used is qualitative research supported by a literature review. The study results suggest two activities that parents and children can do to make their relationship closer, particularly within this pandemic situation. The quality of a good relationship between them will minimize the potential for disharmony and even violence. The two activities are; 1) Indoor Outbound, this activity helps both children and parents feel cooperative and trusting each other through the house’s outbound activity. Direct parental involvement in children will help improve this relationship. This involvement is divided into two, namely partial and whole. 2) Parenting Day, an effort that parents can increase to their children. In children who are still not yet adolescents, the effort is to overcome tantrums and in adolescents is to create effective communication between the two. The author concludes that the main key to preventing child abuse is the quality of the child's relationship with his/ her parents.